Breeding biology of Bewick’s Swans Cygnus bewickii in Chukotka, Far Eastern USSR - Kondratiev, A Ya (Wildfowl, 2013)
Results of long-term research into the breeding biology of Bewickâ€™s Swans in the tundras ofÂ Chukotka are presented. The birds usually begin breeding at the beginning of June, 10-16 days afterÂ arriving in the breeding sites. Clutch size occasionally numbers 6 eggs, and averages 3.84. BothÂ members of the pair incubate, keeping the clutch warm almost all of the time. The male incubatesÂ for 20-50% of the time during the 30 day incubation period. The weight of the newly hatched youngÂ varies from 165 g to 197g, withan average of 177.5 g (63.1-67.1% of the weight of the recently laidÂ eggs). The average brood size is 3.40 just after hatching and 2.96 before the young fledge. YoungÂ Bewickâ€™s Swans are able to fly in early September when they are 45-50 days old.